Factors Related to Nurse's Compliance in Implementation of Standard Operating Procedures for Urethral Catheter Insertion - Grace Jeny Wakanno (MOLUCCAS HEALTH JOURNAL, 2020)
ABSTRACT The act of catheterization in patients with urinary elimination disorders must be based on science and carried out in accordance with the installation sequence or fixed procedure. The purpose of this study was to determine the factors related to nurses' compliance in the implementation of standard operating procedures for urethral catheter placement in Ambon Living Resources Hospital. The analytical descriptive design with cross sectional study was used. The population is all nurses who provide nursing services in the Emergency Room and inpatient rooms of Ambon Life Sources Hospital, which number a population of 40 nurses. Sampling using total sampling technique. The sample in this study amounted to 40 people. There is a correlation between knowledge with nurses 'compliance in the implementation of fixed catheter installation procedures with values (p = 0.013), there is a relationship between attitudes and nurses' compliance in the implementation of fixed catheter installation procedures with a value (p = 0.000), there is a long working relationship with compliance nurses in the implementation of fixed catheter installation procedures with a value (p = 0,000). It is expected that nurses can apply and run in nursing practice regarding compliance with running a Standard Operating Procedure (SOP) for catheter insertion.Â Keywords: Knowledge, Attitude, Length of Work, SOP Catheter